Live births of immigrant mothers in Brazil: A population-based study - Érica Karoline Ferreira; Marcia Furquim de Almeida; Gizelton Pereira Alencar; Zilda Pereira da Silva (Elsevier, 2022)
Introduction: Migration has become a major challenge for many countries, and women constitute half of the migrants in the world. Few studies have been conducted on migrant mothers in Brazil. We aim to identify differences in the pregnancies, childbirths, and live birth (LB) indicators of immigrant women, compared with those of Brazilian women living in the municipality of São Paulo (MSP), Brazil. Methods: The LB characteristics of immigrant mothers from Bolivia (15,886), China (3861), Paraguay (1370), and Peru (1039) were compared with those of Brazilian mothers (967,921) living in the MSP between 2012 and 2017. Pearson's chi-square test was used to compare proportions with a significance level of 5%. Results: Teenage pregnancy and low education were more frequent among Bolivian (13.1 and 31.7%, respectively) and Paraguayan mothers (13.1 and 36.2%). Bolivian women exhibited a high percentage of late-onset prenatal care (8.7%), few prenatal visits (14.3%), vaginal birth (77.0%), home delivery (1.6%), and postterm (3.6%). Bolivian (13.6%), Peruvian (10.6%), and Paraguayan (7.9%) women exhibited a higher prevalence of macrosomia than Chinese (4.3%) and Brazilian (4.0%) women. There was a high prevalence of preterm and low birth weights among Paraguayan (12.5 and 7.7%, respectively) and Brazilian mothers (11.0 and 9.7%) and a high rate of cesarean sections among Chinese (42.1%) and Brazilian (53.5%). Conclusion: Differences were observed in the sociodemographic profiles for the pregnancies, childbirths, and LBs of immigrant mothers, in view of their increase and diversity in the MSP. There was greater vulnerability among immigrant mothers, compared with Brazilian mothers, particularly regarding access to prenatal care.